2013
DOI: 10.1103/physrevb.88.094417
|View full text |Cite
|
Sign up to set email alerts
|

Spin state and orbital ordering in CuCr2O4investigated by NMR

Abstract: 63,65 Cu and 53 Cr nuclear magnetic resonance spectra for CuCr 2 O 4 were measured at various magnetic fields and temperatures. The microscopic evidence of orbital ordering in CuCr 2 O 4 was obtained from a dipolar hyperfine field, NQR, and magnetic anisotropy analysis of the linewidth broadening of the Cu and Cr NMR spectra measured in the external magnetic field. The energy gap in the dispersion relation of the spin wave excitation was measured from the temperature dependence of the resonance frequency of Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…The total magnetic moment of atoms calculated from GGA-PBE and LDA-CA is presented in Table 3. The values of the magnetic moment obtained by the present calculation are slightly higher than the experimental ones [5].…”
Section: Electronic and Magnetic Propertiescontrasting
confidence: 69%
See 1 more Smart Citation
“…The total magnetic moment of atoms calculated from GGA-PBE and LDA-CA is presented in Table 3. The values of the magnetic moment obtained by the present calculation are slightly higher than the experimental ones [5].…”
Section: Electronic and Magnetic Propertiescontrasting
confidence: 69%
“…Several studies on ACr2O4 spinel oxides have been reported in literature [1,3,4]. Ternary normal spinels with stoichiometric composition A 2+ Cr 3+ 2O4 are typical candidates for studying the magnetic properties of frustrated systems [2,[5][6][7][8]. The cations of Cr 3+ at the B site are octahedrally coordinated and form a pyrochlore-type lattice, one of the strongest contenders of geometric frustration in three dimensions [8], while the A-site cations are tetrahedrally coordinated, constituting a diamond-type lattice with tetrahedral oxygen environment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The neutron scattering studies proposed a magnetic structure with a moment of 0.5 μ B per formula unit, where two canted Cr 3+ sublattices and one Cu 2+ sublattice were coupled antiferromagnetically below T N [18,23,24]. The 63,65 Cu and 53 Cr nuclear magnetic resonance studies further confirmed that the angle between the Cr 3+ and the Cu 2+ magnetic moments was found to be ≈98 • [5]. Furthermore, the spin-orbit coupling of Cr ions was proposed to be much stronger than that of Cu ions related to the orbital ordering in CuCr 2 O 4 .…”
Section: Introductionmentioning
confidence: 81%
“…One of the fascinating outcomes is the colossal magnetoresistance in the mixed-valent manganites [1,2]. Moreover, this intricate interplay gives rise to the diverse ranges of the interesting magnetic properties from the frustrated magnetism to the multiferroic properties [3][4][5][6][7][8]. In the above cases, the orbital ordering driven by the the Jahn-Teller (J-T) distortion has been found crucial, which was intimately correlated to the structural distortion and also, eventually, directed the magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…ii) If A 2+ ions are magnetic with spin only, such as MnCr 2 O 4 (S(Mn 2+ )=5/2), [13][14][15][16][17] and CoCr 2 O 4 (S(Co 2+ )=3/2), [13][14][15][16][17][18][19][20][21] the lattice remains cubic, with a paramagnetic-toferrimagnetic transition at high temperature, followed by a transition to spiral ordering at lower temperature due to weak magnetic geometrical frustration. iii) If A 2+ ions are magnetic with the orbital degree of freedom, such as FeCr 2 O 4 , 17,[20][21][22][23][24][25] NiCr 2 O 4 , 17,[21][22][23]26,27 and CuCr 2 O 4 , 17,21,22,[27][28][29] a cubic-tetragonal phase transition is observed at a higher temperature, followed by magnetic order, which indicates that the magnetic ordering is stabilized by reducing the lattice symmetry through a spin-lattice coupling. The long-range ordered collinear ferrimagnetic state can eventually evolve into different noncollinear ferrimagnetic states at a lower temperature, such as conical ordering in FeCr 2 O 4 and NiCr 2 O 4 , and Yafet-Kittel-type magnetic ordering in CuCr 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%